Sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material and preparation method thereof
By controlling the structural regulation of the lead-free ferroelectric ceramic materials based on bismuth titanate, La(Mg1/2Zr1/2)O3 is introduced to form polar nanomicro regions, which solves the problem of insufficient optimization of energy storage performance of existing ceramic materials. , achieving the effect of high energy storage density and high energy storage efficiency.
Patent Information
- Application Number
- CN202311067754.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-08-23
AI Technical Summary
The existing bismuth titanate-based lead-free ferroelectric ceramic materials have shortcomings in energy storage performance optimization, limited energy storage density and energy storage efficiency, and uncertainty in methods to improve performance.
By regulating the structure of ceramic materials, La(Mg1/2Zr1/2)O3 is introduced to form polar nanomicro regions, optimize the microstructure of ceramics, and improve breakdown field strength and energy storage performance.
The high energy storage density and high energy storage efficiency of ceramic materials are achieved, with energy storage density reaching 3.60~5.05J/cm3 and energy storage efficiency of 81.3~91.5%, while improving the thermal stability and environmental friendliness of the material.
Smart Images

Figure CN116986900B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an energy storage ceramic material, in particular to a sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material and a preparation method thereof. Background Art
[0002] With the continuous development of modern science and technology, while providing convenience for people's daily life, it also puts forward higher requirements for electronic information products. Miniaturization, lightweight and smart wearable electronic products have become the trend of future development, and the energy problems associated with this have gradually become the focus of social attention. Based on the above situation, adhering to the call for green and sustainable development, vigorously developing green and clean new energy and new materials and exploring and improving processes have become the focus of current attention, and the development of new energy storage materials to replace traditional energy materials is imminent.
[0003] Sodium bismuth titanate-based lead-free relaxor ferroelectric ceramic materials stand out for their excellent energy storage efficiency and environmental advantages, and are considered to be ideal materials for the preparation of electronic components. Below 220°C, pure NBT ceramics exhibit strong ferroelectric properties. When the temperature rises to above 320°C, the NBT phase structure transforms into a tetragonal paraelectric structure. When the temperature rises to 520°C, the phase structure transforms into a cubic phase, showing obvious relaxation characteristics. In addition, pure NBT has a high remnant polarization at room temperature, which greatly limits its application in the field of dielectric energy storage. Therefore, in recent years, the electrical properties of NBT ceramics have been optimized by optimizing the preparation method of pure NBT and doping components to increase the releasable energy storage density (Wrec) of energy storage ceramic capacitors.
[0004] Zhu et al. published a study in J. Mater. Sci.: Mater. Electron. that doubled the breakdown field strength by adjusting the sintering temperature to obtain 3.88 J / cm 3 High energy storage density. Li et al. published in J.Alloys.Compd. 0.48 La 0.02 Na 0.5 )Ti 0.92 (Al 0.5 Nb 0.5 ) 0.08 O3(BLNANT) and SrTiO3(ST) are regulated to make (1-x)(Bi 0.48 La 0.02 Na 0.5 )Ti 0.92 (Al 0.5 Nb 0.5 ) 0.08O3-xSrTiO3[(1-x)(BLNANT)-xST] ceramics have achieved improved energy storage performance, with energy storage density and energy storage efficiency reaching 3.55 J / cm at a low electric field of 255 kV / cm. 3 and 78%. Obviously, the impact of these methods on energy storage performance is limited. In addition, there is uncertainty in improving performance based on these methods. Therefore, it is of universal significance to explore new strategies to improve energy storage performance through structural engineering. Summary of the invention
[0005] In view of the problem that the energy storage performance of the above-mentioned existing ceramic materials is insufficiently optimized, the present invention provides a sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material and a preparation method thereof. The ceramic material achieves higher energy storage density and energy storage efficiency by regulating its structure.
[0006] In order to achieve the above-mentioned object, the present invention provides a sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material, which comprises a base ceramic having the following chemical formula: (1-x)(0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-xLa(Mg 1 / 2 Zr 1 / 2 )O3, where the value of x ranges from 0.04 to 0.16.
[0007] The present invention regulates the microstructure of ceramic materials to induce NBT (Na 0.5 Bi 0.5 TiO3) based ceramics produce polar nano-micro-regions, thereby obtaining higher energy storage density and energy storage efficiency at room temperature. The specific principles are as follows:
[0008] Pure NBT ceramics have strong ferroelectricity, which makes them show large remnant polarization. 2+ Ions and Nd 3+ The introduction of 0.8NBT-0.2SNT causes the [TiO3] octahedron to be distorted, the electric domain stability is reduced, and the ferroelectric long-range polar coupling is destroyed, thereby reducing the residual polarization at room temperature and improving the thermal stability of the ceramic material.
[0009] (0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 The premature polarization saturation and low breakdown field strength of the TiO3 component lead to poor energy storage performance. 3+The introduction of makes the matrix material form a "pinning effect" at the A position, effectively inhibiting the growth of large grains, making the grain size uniform and small, which greatly improves the breakdown field strength of the matrix material. In addition, for NBT-based ceramics (B1 / B2) 3+ It can induce the formation of polar nano-microregions, improve the ceramic relaxation characteristics, and delay the occurrence of saturation polarization. The substantial increase in breakdown field strength accompanied by the reduction in residual polarization intensity greatly optimizes the energy storage performance of lead-free relaxor ferroelectric materials.
[0010] According to the experimental results, LMZ(La(Mg 1 / 2 Zr 1 / 2 The introduction of LMZ significantly reduces the grain size, which greatly promotes the effective improvement of the breakdown field strength. At this time, the lead-free relaxor ferroelectric ceramic material achieves a significant improvement from 236kV / cm to 440kV / cm. In addition, with the introduction of LMZ, the electric domain structure is significantly reduced, and the residual polarization of the lead-free relaxor ferroelectric ceramic material appears to be 1.64μC / cm 2 To 0.57μC / cm 2 a significant decline.
[0011] Preferably, the value range of x is 0.08 to 0.12.
[0012] When x=0.12, there are multiple polar nano-domains in the ceramic sample, and the domain width is kept at about 1nm. At this time, the lead-free relaxor ceramic dielectric material obtained by the structural design strategy can release a maximum energy storage density of 5.05J / cm 3 , and at this time reached an excellent energy storage efficiency of 90.84%.
[0013] Furthermore, the ceramic material also includes 0.3-0.7wt% of YbO3, 0.07-0.3wt% of Sm2O3, 0.15-0.45wt% of CaO and 0.10-0.45wt% of SiO2, accounting for 0.3-0.7wt% of the base ceramic.
[0014] In the above technical solution, the addition of a small amount of YbO3, Sm2O3, CaO, and SiO2 can effectively increase the stability of the ceramic components.
[0015] Another aspect of the present invention provides a method for preparing a sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material, the preparation method comprising the following steps:
[0016] S1. Weigh Na2CO3, La2O3, MgO, ZrO2, Bi2O3, SrCO3, Nd2O3, and TiO2, mix them by ball milling, and pre-sinter them to obtain (1-x)(0.8Na 0.5 Bi 0.5 TiO3-0.2Sr0.7 Nd 0.2 TiO3)-xLa(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder, wherein the value of x ranges from 0.04 to 0.16;
[0017] S2, mixing the basic ceramic powder obtained in step S1 with a solvent, a dispersant, a binder, and a plasticizer to obtain a casting slurry;
[0018] S3, casting the casting slurry obtained in step S2 to form a ceramic green body, and performing a debinding and sintering process on the green body material to obtain the ceramic material.
[0019] Specifically, in step S1, the pre-sintering treatment conditions are: temperature of 650-950°C, cooling rate of 3-7°C / min, and holding time of 3-4h.
[0020] Specifically,
[0021] In step S2, the solvent is one or more of ethyl acetate, anhydrous ethanol, and butanone, and the mass percentage of the solvent in the base ceramic is 20-50%; and / or
[0022] The dispersant is tributyl phosphate, and its mass percentage in the base ceramic is 0.5-5%; and / or
[0023] The binder is one or more of polyvinyl butyral, polyvinyl alcohol or methyl cellulose, and the mass percentage of the binder in the base ceramic is 3-5%; and / or
[0024] The plasticizer is one or two of polyethylene glycol and phthalate, and the mass percentage of the plasticizer in the basic ceramic is 0.5-5%.
[0025] Specifically, in step S3, the junction temperature is 1120-1170°C.
[0026] Furthermore, step S2 is: ball-milling and mixing 0.3-0.7wt% of YbO3, 0.07-0.3wt% of Sm2O3, 0.15-0.45wt% of CaO and 0.10-0.45wt% of SiO2 accounting for the base ceramic and the basic ceramic powder obtained in step S1 to obtain a casting powder, and mixing the casting powder with a solvent, a dispersant, a binder and a plasticizer to obtain a casting slurry.
[0027] Through the above technical solution, the present invention achieves the following beneficial effects:
[0028] 1. The present invention prepares (1-x)(0.8Na 0.5 Bi0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-xLa(Mg 1 / 2 Zr 1 / 2 )O3, where x = 0.04-0.16, a fine hysteresis loop is obtained at room temperature, and the breakdown field strength of the material is significantly improved, obtaining a higher energy storage performance, and the energy storage density reaches 3.60-5.05 J / cm 3 , the energy storage efficiency is 81.3-91.5%. This nanostructure-based material design strategy has a positive size effect on energy storage performance, promoting the development of ferroelectric series in the field of energy storage. At the same time, it also makes the material promising to become a new generation of environmentally friendly lead-free relaxor ceramic dielectric materials.
[0029] 2. In a preferred technical solution of the present invention, the addition of a small amount of YbO3, Sm2O3, CaO, and SiO2 can effectively increase the stability of the ceramic components.
[0030] 3. The two-step pre-sintering method is used in the preparation process of the lead-free relaxor ceramic material of the present invention, which reduces the grain size and improves the density of the ceramic material to a certain extent, making its hysteresis loop more slender, thereby facilitating obtaining more excellent energy storage performance.
[0031] 4. The material preparation in the present invention does not contain lead, is harmless to the environment, and has a simple preparation process, high operability, and low overall cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the XRD pattern of the sodium bismuth titanate-based lead-free relaxor ferroelectric ceramic material prepared in Examples 5 to 8;
[0033] Figure 2 is a SEM image of the sodium bismuth titanate-based lead-free relaxor ferroelectric ceramic material prepared in Examples 5 to 8;
[0034] Figure 3 is a TEM image of the sodium bismuth titanate-based lead-free relaxor ferroelectric ceramic material prepared in Example 7;
[0035] Figure 4 is the hysteresis loop of the sodium bismuth titanate-based lead-free relaxor ferroelectric ceramic material prepared in Examples 5 to 8 measured at room temperature;
[0036] Figure 5 It is a diagram of energy storage density and energy storage efficiency of sodium bismuth titanate-based lead-free relaxor ferroelectric ceramic materials prepared in Examples 5 to 8. DETAILED DESCRIPTION
[0037] The specific implementation of the present invention is described in detail below in conjunction with the examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0038] Example 1
[0039] (1) According to the stoichiometric ratio, 0.96 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2Zr 1 / 2 )O3 ceramics were weighed. Weigh 99.8% Na2CO3 6.4783g, 99% Bi2O3 28.6056g, 98% TiO2 23.6727g, 99% SrCO3 6.0642g, 99.99% La2O3 1.9719g, 98% MgO 0.2488g, 99.9% Nd2O3 1.9567g, 99% ZrO2 0.7533g, put them into a nylon jar and use a ball mill to mix them evenly with zirconium dioxide balls and alcohol as ball milling media. Then put the powder into a crucible and use a two-step pre-sintering method at 650℃, with a cooling rate of 3℃ / min, and keep warm for 3 hours to obtain 0.96 (0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.
[0040] (2) 50 g of base ceramic powder, 10 g of ethyl acetate, 5 g of anhydrous ethanol, 5 g of butanone, 0.25 g of tributyl phosphate, 1.5 g of polyvinyl butyral, 0.1 g of polyethylene glycol and 0.15 g of phthalate were mixed to obtain a stable casting slurry.
[0041] (3) Casting the obtained casting slurry, cutting and laminating the resulting ceramic green body, debinding the green body material, and sintering the green body material at a sintering temperature of 1120° C. to finally obtain the lead-free relaxor ferroelectric ceramic material.
[0042] Example 2
[0043] (1) According to the stoichiometric ratio, 0.92 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2TiO3)-0.08La(Mg 1 / 2Zr 1 / 2 )O3 ceramics were weighed. 5.7525g of Na2CO3 with a purity of 99.8%, 25.4940g of Bi2O3 with a purity of 99%, 21.0207g of TiO2 with a purity of 98%, 5.3848g of SrCO3 with a purity of 99.99%, 3.6541g of La2O3 with a purity of 98%, 0.4612g of MgO with a purity of 99.9%, 1.7375g of Nd2O3 with a purity of 99%, and 1.3958g of ZrO2 with a purity of 99% were weighed respectively, and they were placed in a nylon jar and mixed evenly using a ball mill with zirconium dioxide balls and alcohol as ball milling media. Subsequently, the powder was placed in a crucible and pre-sintered in two steps at 950°C with a cooling rate of 7°C / min for 4 hours to obtain 0.96 (0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.
[0044] (2) 50 g of the base ceramic powder was mixed with 10 g of ethyl acetate, 10 g of anhydrous ethanol, 5 g of butanone, 2.5 g of tributyl phosphate, 2.5 g of polyvinyl butyral, 1.4 g of polyethylene glycol and 1.1 g of phthalate to obtain a stable casting slurry.
[0045] (3) Casting the obtained casting slurry, cutting and laminating the resulting ceramic green body, debinding the green body material, and sintering the green body material at a sintering temperature of 1170° C. to finally obtain the lead-free relaxor ferroelectric ceramic material.
[0046] Example 3
[0047] (1) According to the stoichiometric ratio, 0.88 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.12La(Mg 1 / 2Zr 1 / 2)O3 ceramics were weighed. 5.9087g of Na2CO3 with a purity of 99.8%, 26.1865g of Bi2O3 with a purity of 99%, 21.5917g of TiO2 with a purity of 98%, 5.5311g of SrCO3 with a purity of 99.99%, 0.7429g of MgO with a purity of 98%, 1.7847g of Nd2O3 with a purity of 99%, and 2.2484g of ZrO2 with a purity of 99%. They were placed in a nylon jar and mixed evenly using a ball mill with zirconium dioxide balls and alcohol as ball milling media. The powder was then placed in a crucible and pre-sintered in two steps at 750°C with a cooling rate of 5°C / min for 3.5 hours to obtain 0.96 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.
[0048] (2) 50 g of base ceramic powder, 15 g of ethyl acetate, 1 g of tributyl phosphate, 2 g of polyvinyl alcohol, and 0.5 g of polyethylene glycol were mixed to obtain a stable casting slurry.
[0049] (3) Casting the obtained casting slurry, cutting and laminating the resulting ceramic green body, debinding the green body material, and sintering the green body material at a sintering temperature of 1150° C. to finally obtain the lead-free relaxor ferroelectric ceramic material.
[0050] Example 4
[0051] (1) According to the stoichiometric ratio, 0.84 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.16La(Mg 1 / 2Zr 1 / 2)O3 ceramics were weighed. 5.0717g of Na2CO3 with a purity of 99.8%, 22.4765g of Bi2O3 with a purity of 99%, 18.5326g of TiO2 with a purity of 98%, 4.7475g of SrCO3 with a purity of 99%, 7.0569g of La2O3 with a purity of 99.99%, 0.8907g of MgO with a purity of 98%, 1.5319g of Nd2O3 with a purity of 99%, and 2.6957g of ZrO2 with a purity of 99% were weighed respectively, and they were placed in a nylon jar and mixed evenly using a ball mill with zirconium dioxide balls and alcohol as ball milling media. Subsequently, the powder was placed in a crucible and pre-sintered in two steps at 850°C with a cooling rate of 6°C / min for 3 hours to obtain 0.96 (0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.
[0052] (2) 50 g of base ceramic powder, 10 g of anhydrous ethanol, 10 g of butanone, 1.5 g of tributyl phosphate, 2 g of methyl cellulose, 1 g of polyethylene glycol and 1 g of phthalate were mixed to obtain a stable casting slurry.
[0053] (3) Casting the obtained casting slurry, cutting and laminating the resulting ceramic green body, debinding the green body material, and sintering the green body material at a sintering temperature of 1150° C. to finally obtain the lead-free relaxor ferroelectric ceramic material.
[0054] Example 5
[0055] (1) According to the stoichiometric ratio, 0.96 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2Zr 1 / 2)O3 ceramics were weighed. Weigh 99.8% pure Na2CO3 6.1698g, 99% Bi2O3 27.2434g, 98% TiO2 22.5455g, 99% SrCO3 5.7755g, 99.99% La2O3 1.8780g, 98% MgO 0.2370g, 99.9% Nd2O3 1.8636g, 99% ZrO2 0.7174g, put them into a nylon jar and use a ball mill to mix them evenly with zirconium dioxide balls and alcohol as ball milling media. Then put the powder into a crucible and use a two-step pre-sintering method at 650℃, with a cooling rate of 3℃ / min, and keep warm for 3 hours to obtain 0.96 (0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.
[0056] (2) 0.255 g of YbO3, 0.085 g of Sm2O3, 0.15 g of CaO, 0.12 g of SiO2 and 50 g of basic ceramic powder were ball-milled to obtain a casting powder, and the casting powder was mixed with 10 g of ethyl acetate, 5 g of anhydrous ethanol, 5 g of butanone, 0.25 g of tributyl phosphate, 1.5 g of polyvinyl butyral, 0.1 g of polyethylene glycol and 0.15 g of phthalate to obtain a stable casting slurry.
[0057] (3) Casting the obtained casting slurry, cutting and laminating the resulting ceramic green body, debinding the green body material, and sintering the green body material at a sintering temperature of 1120° C. to finally obtain the lead-free relaxor ferroelectric ceramic material.
[0058] Example 6
[0059] (1) According to the stoichiometric ratio, 0.92 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.08La(Mg 1 / 2Zr 1 / 2)O3 ceramics were weighed. Weigh 99.8% Na2CO3 5.8699g, 99% Bi2O3 26.0143g, 98% TiO2 21.4497g, 99% SrCO3 5.4947g, 99.99% La2O3 3.7287g, 98% MgO 0.4706g, 99.9% Nd2O3 1.7730g, 99% ZrO2 1.4243g, put them into a nylon jar and use a ball mill to mix them evenly with zirconium dioxide balls and alcohol as ball milling media. Then put the powder into a crucible and use a two-step pre-sintering method at 950℃, with a cooling rate of 7℃ / min, and keep warm for 4 hours to obtain 0.96 (0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.
[0060] (2) 0.15 g YbO3, 0.15 g Sm2O3, 0.225 g CaO, 0.05 g SiO2 and 50 g basic ceramic powder were ball-milled to obtain a casting powder, and the casting powder was mixed with 10 g ethyl acetate, 10 g anhydrous ethanol, 5 g butanone, 2.5 g tributyl phosphate, 2.5 g polyvinyl butyral, 1.4 g polyethylene glycol and 1.1 g phthalate to obtain a stable casting slurry.
[0061] (3) Casting the obtained casting slurry, cutting and laminating the resulting ceramic green body, debinding the green body material, and sintering the green body material at a sintering temperature of 1170° C. to finally obtain the lead-free relaxor ferroelectric ceramic material.
[0062] Example 7
[0063] (1) According to the stoichiometric ratio, 0.88 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.12La(Mg 1 / 2Zr 1 / 2)O3 ceramics were weighed. Weigh 99.8% Na2CO3 5.5743g, 99% Bi2O3 24.7043g, 98% TiO2 20.3695g, 99% SrCO3 5.2180g, 99.99% La2O3 5.5528g, 98% MgO 0.7009g, 99.9% Nd2O3 1.6837g, 99% ZrO2 2.1211g, put them into a nylon jar and use a ball mill to mix them evenly with zirconium dioxide balls and alcohol as ball milling media. Then put the powder into a crucible and use a two-step pre-sintering method at 750℃, a cooling rate of 5℃ / min, and keep warm for 3.5 hours to obtain 0.96 (0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.
[0064] (2) 0.35 g YbO3, 0.035 g Sm2O3, 0.075 g CaO, 0.05 g SiO2 and 50 g basic ceramic powder are ball-milled to obtain a casting powder, and the casting powder is mixed with 15 g ethyl acetate, 1 g tributyl phosphate, 2 g polyvinyl alcohol and 0.5 g polyethylene glycol to obtain a stable casting slurry.
[0065] (3) Casting the obtained casting slurry, cutting and laminating the resulting ceramic green body, debinding the green body material, and sintering the green body material at a sintering temperature of 1150° C. to finally obtain the lead-free relaxor ferroelectric ceramic material.
[0066] Example 8
[0067] (1) According to the stoichiometric ratio, 0.84 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.16La(Mg 1 / 2Zr 1 / 2)O3 ceramics were weighed. 5.2830g of Na2CO3 with a purity of 99.8%, 23.4130g of Bi2O3 with a purity of 99%, 19.3048g of TiO2 with a purity of 98%, 4.9453g of SrCO3 with a purity of 99.99%, 7.3509g of La2O3 with a purity of 99.99%, 0.9278g of MgO with a purity of 98%, 1.5957g of Nd2O3 with a purity of 99%, and 2.8080g of ZrO2 with a purity of 99% were weighed respectively, and they were placed in a nylon jar and mixed evenly using a ball mill with zirconium dioxide balls and alcohol as ball milling media. Subsequently, the powder was placed in a crucible and pre-sintered in two steps at 850°C with a cooling rate of 6°C / min for 3 hours to obtain 0.96 (0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.04La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.
[0068] (2) 0.15 g YbO3, 0.05 g Sm2O3, 0.3 wt% CaO, 0.175 g SiO2 and 50 g basic ceramic powder are ball-milled to obtain a casting powder, and the casting powder is mixed with 10 g anhydrous ethanol, 10 g butanone, 1.5 g tributyl phosphate, 2 g methyl cellulose, 1 g polyethylene glycol and 1 g phthalate to obtain a stable casting slurry.
[0069] (3) Casting the obtained casting slurry, cutting and laminating the resulting ceramic green body, debinding the green body material, and sintering the green body material at a sintering temperature of 1150° C. to finally obtain the lead-free relaxor ferroelectric ceramic material.
[0070] Reference Figure 1 , that is, the XRD patterns of the relaxor ferroelectric ceramic samples prepared by the processes of Examples 5 to 8. The XRD patterns show that the relaxor ferroelectric ceramic samples of Examples 5 to 8 are pure perovskite structures without secondary phases, indicating that with the increase of La(Mg 1 / 2 Zr 1 / 2 The introduction of )O3 has no significant effect on the sodium bismuth titanate-based structure. Figure 2 , i.e., the SEM images and grain size distribution histograms of the relaxor ferroelectric ceramic samples prepared under the processes of Examples 5 to 8. The SEM spectrum shows that the relaxor ferroelectric ceramic sample with x=0.04, i.e., Example 5, has a relatively loose microstructure. As the LMZ content continues to increase, the degree of densification of the ceramic increases. In addition, the average grain size decreases from 1.27μm to 0.88μm. Smaller grain size and denser microstructure are conducive to obtaining higher energy storage performance. Reference Figure 3TEM image of the relaxor ferroelectric ceramic sample with the best component x=0.12, i.e. the sample prepared by the process of Example 7. When x=0.12, the ceramic sample has multiple polar nano-domains, and the domain width is kept at about 1 nm. Figure 4 , that is, the PE hysteresis loop of the relaxor ferroelectric ceramic samples prepared under the process of Examples 5 to 8 at 10 Hz. It can be seen from the figure that as La(Mg 1 / 2 Zr 1 / 2 ) The increase in O3 content greatly delays the saturation polarization, significantly improving the relaxation characteristics and breakdown field strength, and ultimately greatly improving the energy storage performance of the lead-free relaxor ferroelectric ceramics in this example. Figure 5 That is, the energy storage density and energy storage efficiency of the relaxor ferroelectric ceramic samples prepared by the processes of Examples 5 to 8 increase with the increase of La(Mg 1 / 2 Zr 1 / 2 )O3 content change spectrum. It can be seen from the figure that La(Mg 1 / 2 Zr 1 / 2 ) The energy storage density increases with the increase of O3 content. When x = 0.12, the energy storage density reaches the maximum, at which time 5.05 J / cm 3 Excellent energy storage density and outstanding energy storage efficiency of 90.84%.
[0071] The preferred implementation modes of the present invention are described in detail above in combination with the embodiments; however, the present invention is not limited to the specific details in the above implementation modes. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical scheme of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0072] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0073] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material, characterized in that: The ceramic material includes a base ceramic having the following general chemical formula: 0.88(0.8Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.12La(Mg 1 / 2 Zr 1 / 2 )O3, and 0.3~0.7wt% of YbO3, 0.07~0.3wt% of Sm2O3, 0.15~0.45wt% of CaO and 0.10~0.45wt% of SiO2 accounting for the base ceramic.
2. The method for preparing the sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material according to claim 1, characterized in that: The steps include: S1. Weigh Na2CO3, La2O3, MgO, ZrO2, Bi2O3, SrCO3, Nd2O3, and TiO2, mix them by ball milling, and pre-sinter them to obtain 0.88 (0.8 Na 0.5 Bi 0.5 TiO3-0.2Sr 0.7 Nd 0.2 TiO3)-0.12La(Mg 1 / 2 Zr 1 / 2 )O3 matrix ceramic powder; S2, ball-milling 0.3-0.7wt% of YbO3, 0.07-0.3wt% of Sm2O3, 0.15-0.45wt% of CaO and 0.10-0.45wt% of SiO2 of the base ceramic powder and the base ceramic powder obtained in step S1 to obtain a tape-casting powder, and mixing the tape-casting powder with a solvent, a dispersant, a binder and a plasticizer to obtain a tape-casting slurry; S3, casting the casting slurry obtained in step S2 to form a ceramic green body, and performing a debinding and sintering process on the green body material to obtain the ceramic material.
3. The preparation method according to claim 2, characterized in that: In step S1, the pre-sintering treatment conditions are: temperature of 650-950°C, cooling rate of 3-7°C / min, and holding time of 3-4h.
4. The preparation method according to claim 2, characterized in that: In step S2, the solvent is one or more of ethyl acetate, anhydrous ethanol, and butanone, and the mass percentage of the solvent in the base ceramic is 20-50%; and / or The dispersant is tributyl phosphate, and its mass percentage of the base ceramic is 0.5-5%; and / or The binder is one or more of polyvinyl butyral, polyvinyl alcohol or methyl cellulose, and the weight percentage of the binder in the base ceramic is 3-5%; and / or The plasticizer is one or two of polyethylene glycol and phthalate, and the mass percentage of the plasticizer in the base ceramic is 0.5-5%.
5. The preparation method according to claim 2, characterized in that: In step S3, the sintering temperature is 1120-1170°C.
Citation Information
Patent Citations
Pulse energy storage ceramic material and preparation method thereof
CN112745118A